Penerapan Sikap Kerja 5S (Seiri, Seiton, Seiso, Seiketsu, dan Shitsuke) di Balai Desa Suko Mulyo, Sepaku, Penajam Paser Utara (PPU) - Manaseh Manaseh; Novia Febryantri Wahono; Putri Amelia; Wahyunita Putri Ardini; Poetra Aizhul Haq Oktavian; Rizki Prasetya; Puspita Caroline; Prastio Tri Utomo; Riani Agustin; Oky Dwi Mardani; Syarifa Annisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Real Work Lectures (KKN) is a community service by going directly into the field carried out by lecturers and students. In providing service to the Suko Mulyo Village community, the Balikpapan University P2-B group implemented 5S at the village hall. 5S (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) is a series of workplace activities in the form of selecting, arranging, cleaning, stabilizing and habituating activities which are all needed to carry out good work. The aim of this community service is to be able to implement the application of 5S (Seiri, Seiton, Seiso, Seiketsu and Shitsuke) at the Village Hall, to know how to reduce waste by implementing 5S (Seiri, Seiton, Seiso, Seiketsu and Shitsuke ) at the Village Hall, and to find out the differences in the 5S work attitude before and after it was implemented and increased productivity, safety, occupational health and consumer satisfaction at the village hall. This community service uses the 5S method approach. It is hoped that the results of the community seervice will show that the implementation of 5S can bring positive perceptions, which means a shift in work culture towards a better direction. So the implementation of 5S needs continuity so that it can survive and provide even better results.